PERSEPSI TENTANG PANGAN SEHAT, ALASAN PEMILIHAN PANGAN DAN KEBIASAAN MAKAN SEHAT PADA MAHASISWA - Puspadewi, Rekyan Hanung; Briawan, Dodik (Jurnal Gizi dan Pangan, 2014)
The study aimed to determine perception of healthy food, motives of food choices and healthy eating in undergraduate students. The design of this study was a cross sectional study with the total subjects were 120 freshman undergraduate students in nutrition sciences batch 2013/2014 in Bogor Agricultural University, consisted of 103 females and 17 males. The motives food choice was assessed by Food Choice Questionnaire (FCQ) and the healthy eating was assessed by Adolescent Food Habits Checklist (AFHC). The results showed that nutritional status of subjects was categorized as normal (81.7%), overweight (13.3%) and underweight (5.0%). The most category in the food perception of healthy food was neutral (77.5%), and this perception was at the level doubt to agree on criteria for healthy food. The main reasons of the subjects in choosing foods were on the aspects of natural content, health and price. Most of subjects were categorized in a good healthy eating (54.2%), they concerned about consumption of fruits and vegetables, as`well as intake of fat and sugar. The perception about healthy food was correlated with the reason in choosing foods (health, mood, natural content, price, familiarity, and ethics concern) (p<0.05). There was a correlation between the reason in choosing foods (health, mood, natural content, weight control, ethics concern) with the score of healthy eating (p<0.05). The overweight and obese adolescent has a healthier perception of food and eating compared than the normal subjects.